(untitled) (Mūzikas akadēmijas raksti, 2024)
During our epoch of globalization where any national art is threatened, where any diversifying characteristic national element is absorbed under the flux of cultural homogenization, the relation between musical work and national identity as well as the role of the contemporary composer must be reviewed. In this article, we will examine the relation between musical work and national identity in the 19th century and 20th century, through a comparative critical analysis of musical works and literary texts, specifically chosen by representative composers of these periods, such as Richard Wagner, Robert Schumann, Manolis Kalomoiris, Mikis Theodorakis, etc. Secondly, we will define the musical elements that transformed their works – expressing the ‘national soul’– to ecumenical. Finally, we will highlight how the idea of ‘national identity’ is expressed nowadays through the works of Greek and German contemporary composers.